1996
DOI: 10.1007/s002130050103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of benzodiazepine receptor heterogeneity in vivo: apparent pA 2 and pK B analyses from behavioral studies

Abstract: The purpose of this review was to establish in vivo apparent pA2 and pKB values for antagonism of the discriminative stimulus effects of benzodiazepine ligands, and to compare these values to those obtained from other behavioral procedures. Articles were chosen from the Medline data base from January 1976 to August 1995. This literature consisted of studies with flumazenil (Ro 15-1788) as the antagonist, as well as other benzodiazepine ligands (beta-carbolines, CGS 9896, CGS 8216). The dose which occasioned 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…Another possibility is that the difference from -1.0 in the slope of the Schild plot obtained in the current study is due to behavioral effects of flumazenil which have been demonstrated in some procedures (Haefely 1988;Rowlett and Woolverton 1996). However, it might be expected that the intrinsic efficacy of flumazenil would similarly affect antagonism of both zolpidem and triazolam.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another possibility is that the difference from -1.0 in the slope of the Schild plot obtained in the current study is due to behavioral effects of flumazenil which have been demonstrated in some procedures (Haefely 1988;Rowlett and Woolverton 1996). However, it might be expected that the intrinsic efficacy of flumazenil would similarly affect antagonism of both zolpidem and triazolam.…”
Section: Discussionmentioning
confidence: 63%
“…However, despite orderly dose-dependent shifts to the right in the triazolam dose-effect curves, the slope of the Schild plot was different from unity. At least three possibilities could account for this apparent lack of competitive interaction: non-equilibrium conditions, intrinsic efficacy of flumazenil, or multiple BZ receptors mediating the triazolam DS (Rowlett and Woolverton 1996;Kenakin 1997). In the present study, flumazenil was administered at the same pretreatment time and by the same route as in the zolpidem study, in which the slope of the Schild plot was not different from unity (Rowlett et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Apparent pK B quantifies shifts in each dose-response function after Ro15-4513 or flumazenil pretreatment and estimates the affinity of Ro15-4513 and flumazenil for the receptor population mediating the effects of the test drug (e.g., Rowlett and Woolverton, 1996). When three or more shifts in the dose-response function were obtained, apparent pA 2 was calculated to more accurately assess Ro15-4513 and flumazenil affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Potency ratios were calculated to determine whether there were sex differences in the degree to which rimonabant shifted agonist dose-effect curves (Pharm/PCS, version 4.2). Finally, apparent pK B values were determined to provide an estimate of rimonabant affinity in females versus males: pK B ϭ Ϫlog [B/(dose ratio Ϫ 1)], where B is the antagonist dose in moles/kilogram and dose ratio is the ED 50 antagonist ϩ agonist/ED 50 vehicle ϩ agonist (Negus et al, 1993;Rowlett and Woolverton, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate a pharmacodynamic mechanism underlying sex differences in agonist/antagonist interaction in the present study, complete agonist dose-effect curves were obtained, alone and in combination with the most effective doses of each antagonist. In vivo apparent pK B values (Negus et al, 1993;Rowlett and Woolverton, 1996) were calculated from these curves to test the hypothesis that sex differences in behavioral effects of cannabinoid drugs are caused by sex differences in the affinity of cannabinoid drugs for cannabinoid receptors. The time course of antagonist effect as well as plasma levels of antagonist were examined to determine whether sex differences in antagonism of cannabinoid agonistinduced behaviors could be attributed to sex differences in antagonist duration of action or absorption.…”
Section: Introductionmentioning
confidence: 99%